Legal Challenges In The Implementation Of Change In The Authority To Issue Certificates of Inheritance After Ministry of Agrarian Affairs and Spatial Planning Regulation Number 16 Of 2021 - Bunga Jasmine Puji Hapsari; Shofiy Zulfah (KRTHA BHAYANGKARA, 2025)
This research discusses legal issues arising in the implementation of changes in the authority to issue a Certificate of Inheritance after the enactment of Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 16 of 2021, which is the third amendment to Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 9 of 1999 on Procedures for Granting and Cancelling State Land Rights and Management Rights. Using sociological juridical approach, this study analyses the implications of the change in authority on the inheritance law system in Indonesia, conflicts of norms arising from dualism of authority, and aspects of legal certainty for the community. The results show that the changes pose significant challenges in harmonising regulations related to the authority to issue Certificate of Inheritance, gaps in implementation in the field, and potential legal uncertainty. Research recommendations include regulatory harmonisation, strengthening inter-agency coordination, and developing an integrated system for inheritance administration.